Evaluation of thyromental distance versus tongue width versus weight-based method for size determination of laryngeal mask airway in adults - Shalini Jain,; Joshi, Priyanka; K K Arora, (Asian Journal of Medical Sciences, 2023)
Background: Supraglottic airway devices (SGD) are indispensable for airway management. The successful placement of the laryngeal mask airway (LMA) supreme largely depends on the right size selection. Aims and Objectives: The study was undertaken to compare three LMA supreme insertion methods in short elective surgeries under general anesthesia. Materials and Methods: Atotal of 90 American Society of Anesthesiologists I and II patients (either gender, 18–55 years, Mallampati grade I and II) undergoing short surgeries were randomized into three equal groups (n=30 in each). Insertion of LMA was done after an adequate depth of anesthesia for jaw relaxation (Young’s criteria). The efficacy of controlled ventilation through LMA by each method, success rate, ease of insertion, insertion time, additional induction dose (propofol) required during insertion, hemodynamic stability (baseline vitals and 10 min after insertion), and adverse events after LMA removal were evaluated between groups. Results: Better ventilation (tidal volume at 10 cmH2O) was observed in the thyromental group (448±35) than in tongue width (440±46) and weight-based (409±33) groups. Minimum additional propofol requirement during insertion was in thyromental distance group. Thyromental distance group had the most easy LMA insertions (70%) with minimum insertion time (10±4) and minimum additional propofol requirement during insertion (P<0.05) than other groups. Overall hemodynamic stability and incidence of adverse events were comparable. Conclusion: Thyromental distance may be an alternative attractive choice for size determination of LMA supreme in female adults with normal airway anatomy in comparison to tongue width and conventional body weight-based methods.